Leadership influence on institutional transformation in the post-merger and incorporation era: A case of the Durban University of Technology - Ngcamu, Bethuel Sibongiseni; Damtew Teferra, Damtew Teferra (South African Journal of Higher Education, 2016)
This study investigates leadership features that have the potential to influence transformation, post-merger and incorporation of the Durban University of Technology (DUT). The post-merger era of HEIs (HEIs) in South Africa has been clouded by a multiplicity of challenges, including lack of interpersonal skills by the university leaders. This study takes a quantitative approach through a structured survey questionnaire administered to 191 university leaders. The questionnaires generated the reliability coefficient Alpha of 0.947, which indicates the high degree of acceptance and consistency of the results. There was only 10% difference between the research participants who concurred with and those who disputed that university leaders were prepared to listen. Almost half (48%) perceived that university leaders are proactive from the top. This study will contribute to the body of knowledge as there is a dearth of published information on leadership features that could drive transformation post-merger and incorporation era. This study will further assist human resources practitioners and higher education subject specialists in designing relevant leadership development programmes focusing on leadership capabilities that could assist to achieve both the institutional and national transformation agenda.